Multidisciplinary Management of Common Bile Duct Stones - Hazey, Jeffrey W.; Conwell, Darwin L.; Guy, Gregory E. (Springer International Publishing : Imprint: Springer, 2016)
This volume is a single resource highlighting multidisciplinary options available to clinicians for the management of common bile duct stones. The text highlights management, diagnosis, treatment options, and complications from the perspective of surgeons, gastroenterologists, and interventional radiologists, providing a truly multidisciplinary approach to treatment of these patients. By providing the scope of the problem to clinicians, the text increases awareness such that testing or referral to the most appropriate specialist (whether it be a gastroenterologist, surgeon or radiologist) can be initiated.    Providing surgeons, gastroenterologists and radiologists alike access to the most current treatment paradigms in their field, Multidisciplinary Management of Common Bile Duct Stones empowers healthcare providers with interdisciplinary knowledge and options available to patients in management of their common bile duct stones. .